Relief, Recovery, Reform: A Retrospective on the US Policy Responses to the Great Recession - Basak Kus (Intereconomics, 2020)
The Great Recession presented the US with economic and political challenges that had not been experienced since the time of the Great Depression. This article provides a retrospective on the government's response to the crisis ten years after the enactment of the Dodd-Frank Act, as the country is heading into its next presidential election in the midst of yet another downturn, this time fueled by the COVID-19 pandemic.
Keywords: 330